Does change in risk matter?: examining whether changes in offender risk characteristics influence recidivism outcomes - Cohen, Thomas (Criminology & public policy, 2016)
The Post Conviction Risk Assessment (PCRA) is a correctional assessment tool used by federal probation officers that identifies offenders most likely to commit new crimes and the criminogenic characteristics that, if changed, could reduce the likelihood of recidivism. We explored how changes in offender risk influence the likelihood of recidivism by tracking a population of 64,716 offenders placed on federal supervision with multiple PCRA assessments. In general, offenders scoring in the high‐, moderate‐, and low/moderate‐risk categories at their initial assessment and experiencing decreases in their risk classifications were less likely to recidivate compared with their counterparts whose risk levels remained unchanged or increased. Conversely, increases in offender risk were associated with higher rates of reoffending behavior. Notably, we saw no recidivism reduction for offenders in the lowest risk category if they received decreases in their overall PCRA scores.